2020
DOI: 10.1080/22221751.2020.1754134
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel bacterial receptor that binds tail tubular proteins and mediates phage infection of Vibrio parahaemolyticus

Abstract: The adsorption of phages to hosts is the first step of phage infection. Studies have shown that tailed phages use tail fibres or spikes to recognize bacterial receptors and mediate adsorption. However, whether other phage tail components can also recognize host receptors is unknown. To identify potential receptors, we screened a transposon mutagenesis library of the marine pathogen Vibrio parahaemolyticus and discovered that a vp0980 mutant (vp0980 encodes a predicted transmembrane protein) could not be lysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 65 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…Tubular protein A is responsible for the attachment of the fibers, while tail tubular B forms the end of the tail [ 45 ]. In addition to their structural function, recent studies suggest that the tail tubular proteins have a role in host recognition and attachment to its surface [ 46 , 47 ]. Furthermore, the tail tubular protein A of the Klebsiella pneumoniae phage KP32 was found to exhibit lytic activity towards exopolysaccharide [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tubular protein A is responsible for the attachment of the fibers, while tail tubular B forms the end of the tail [ 45 ]. In addition to their structural function, recent studies suggest that the tail tubular proteins have a role in host recognition and attachment to its surface [ 46 , 47 ]. Furthermore, the tail tubular protein A of the Klebsiella pneumoniae phage KP32 was found to exhibit lytic activity towards exopolysaccharide [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Baudoux et al (2012) revealed that a Vibrio siphovirus bacteriophage SIO-2 was identified with the presence of a major capsid protein with a molecular mass of 29 kDa. Other protein bands may indicate the presence of putative tail fiber protein (32.7 kDa), putative scaffolding protein (30.1 kDa), putative internal virion protein B (20.4 kDa), hypothetical and/or unknown proteins of Vibrio bacteriophage (Drulis-Kawa et al, 2012;Hu et al, 2020). Bacteriophages rely on the chance of meeting with bacteria to infect and kill bacteria (Huff et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It forms an attachment for tail spikes to mediate infection through sensing the deflection of side fibers upon cell-wall binding. During infection by bacteria, TPPA can bind with bacterial receptors to mediate bacteriophage adsorption and subsequent bacterial lysis ( Hu et al., 2020 ; Pyra et al., 2020a ; Pyra et al., 2020b ). If differences occur specifically in the genes encoding the tail fibers, then recognition of the cell target will change ( Vacheron et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The average nucleotide identity (ANI) was determined among all pairwise combinations of phage genomes. The assembly sequence was evaluated and corrected with PhageTerm ( Hu et al., 2020 ), putative open reading frame (ORF) was predicted by Prokka 1.1.3. The annotated genome sequence of the bacteriophage YepMm has been deposited into the National Center for Biotechnology Information GenBank database under the accession numbers MW767996 and BankIt 2439990.…”
Section: Methodsmentioning
confidence: 99%